Mewujudkan Perubahan Positif Melalui Kewirausahaan Sosial yang Kreatif dan Inovatif - Purwaningsih, Dewi; Wahyuningsih, Bibit Deny (CV RIFAINSTITUT, 2025)
Social entrepreneurship has grown rapidly as a solution to overcome various social and environmental problems. In the midst of increasingly complex social challenges, creative and innovative social entrepreneurship can be an effective means to create positive change, empower communities, and improve social welfare. This study aims to identify the role of creative and innovative social entrepreneurship in realizing positive change in society. This study also seeks to understand the factors that influence the success of social entrepreneurship in providing significant social impacts. The research method used is a qualitative approach with interview techniques. The overall results of the study, creative and innovative social entrepreneurship can be a catalyst for significant positive change for society. Training, mentoring, and strengthening networks are needed to strengthen the impact of social entrepreneurship. In the future, collaboration between the government, private sector, and society will be an important element to accelerate the spread of wider social impacts.